ANALISIS EFISIENSI BIAYA PEMELIHARAAN MESIN ROBOT WELDING MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) DI PT. XYZ - Hardi Elfandi; Yayan Heru Haerudin; Rizky Fajar Ramdhani (STKIP Pesisir Selatan, 2026)
The Robot Welding machine is one of the primary production equipment at PT. XYZ with a high utilization rate, requiring an effective maintenance system to ensure its operational reliability. The existing maintenance system is predominantly based on corrective maintenance, resulting in recurring failures, increased downtime, and higher maintenance costs. This study aims to identify critical components, determine appropriate maintenance strategies using the Reliability Centered Maintenance (RCM) method, and analyze maintenance cost efficiency. The research employs the Reliability Centered Maintenance (RCM) approach supported by Failure Mode and Effects Analysis (FMEA), Risk Priority Number (RPN), and Logic Tree Analysis (LTA). The analysis identified four critical components: Contact Tip, O-ring, Feeder Roller, and Conduit Cable (Liner). Based on the RCM Decision Worksheet, the Contact Tip is recommended for Time-Based Maintenance (TBM), while the O-ring, Feeder Roller, and Conduit Cable (Liner) are recommended for Condition-Based Maintenance (CBM). The maintenance cost analysis indicates that the total corrective maintenance cost was IDR 5,177,177, whereas the proposed preventive maintenance cost was reduced to IDR 4,650,000, resulting in a cost saving of IDR 527,177 or approximately 10.18%. The findings demonstrate that the implementation of the Reliability Centered Maintenance method can improve the effectiveness of the maintenance system while reducing maintenance costs for the Robot Welding machine at PT. XYZ.